Laboratory animals as surrogate models of human obesity - Nilsson, Cecilia (Nature Publishing Group, 2012)
Obesity and obesity-related metabolic diseases represent a growing socioeconomic problem throughout the world. Great emphasis has been put on establishing treatments for this condition, including pharmacological intervention. However, there are many obstacles and pitfalls in the development process from pre-clinical research to the pharmacy counter, and there is no certainty that what has been observed pre-clinically will translate into an improvement in human health. Hence, it is important to test potential new drugs in a valid translational model early in their development. In the current mini-review, a number of monogenetic and polygenic models of obesity will be discussed in view of their translational character.